THE SAVIOUR ARCHETYPE: A STUDY IN TI-IE ESCHATOLOGICAL VISION OF RELIGIONS - Gier, Nicholas (Journal of Dharma, 1979)
One of the most significant discoveries of the science of comparative religion has been what I shall call the "Saviour Archetype." Before we begin the analysis proper let me define the phrase carefully. First, the word" saviour" (from the Latin Salvo = to save) means one who "saves" humankind, one who redeems them from sin and death. Second, the word "archetype" (from the Greek archetypon = first type) means an original pattern or formal outline. I am not using the term in its Jungian sense; that is, I am not holding any of the questionable assumptions of Jungian psychology